ARTIFICIAL INTELLIGENCE AS AN EFFECTIVE MEANS OF ORGANIZING TEACHING FOR STUDENTS WITH DISABILITIES - Hovhannisyan, N. (SUSh Scientific Proceedings, 2025)
This article presents the importance of artificial intelligence (AI) in teaching students with disabilities. AI-powered systems offer personalized and accessible solutions that can meet the learning needs of students. AI can help tailor learning content to students’ individual learning pace, style, and abilities, helping to create an inclusive and supportive environment. It can provide realtime feedback, track progress, and help educators overcome various learning challenges. Additionally, AI-powered tools such as speech recognition and text-to-speech programs can help students with physical and sensory impairments participate more effectively in the learning process. AI-powered systems provide greater accessibility, flexibility, and efficiency, promoting inclusion and equal learning opportunities for all students. The article also analyzes the results of surveys conducted among students with disabilities. The scientific novelty of the article is the development of ways to integrate various advanced systems based on artificial intelligence and improve the quality of learning, which will allow to personalize the learning process, by increasing its accessibility and optimizing teaching methods for students with disabilities.